A comparison of the mechanisms and performances of Acorus calamus, Pontederia cordata and Alisma plantagoaquatica in removing nitrogen from farmland wastewater. (July 2021) - He, Shifu; Li, Yan; Yang, Wei; Huang, Jiayi; Hou, Kun; Zhang, Lian; Song, Haixing; Yang, Lan; Tian, Chang; Rong, Xiangmin; Han, Yongliang
Graphical abstract: Highlights: Constructed wetlands with aquatic plants completed 90% N removal in the first 10 days. The N removal via plant uptake was high at 2.109–10.379 g m −2 . The proportion of N removed via microbial process reached 49.9–86.4%. Plants can increase N2 O emissions from constructed wetlands by 157.6–250.2%. Abstract: This study examined the performances of Acorus calamus, Pontederia cordata, and Alisma plantagoaquatica in removing nitrogen (N) from farmland wastewater. P. cordata showed the fastest rate of N removal, followed by A. plantagoaquatica, whereas that of A. calamus was slowest. P. cordata and A. plantagoaquatica achieving a greater rate of TN reduction in soil than that by A. calamus . A. plantagoaquatica demonstrated the highest N adsorption capacity, 32.6% and 392.1% higher than that of P. cordata and A. calamus, respectively. The higher potential nitrification and denitrification rate, and abundance of functional genes in the P. cordata microcosm resulted in a stronger process of nitrification–denitrification, which accounted for 65.99% of TN loss. Plant uptake and nitrification–denitrification were responsible for 50.06% and 49.94% of TN removed within the A. plantagoaquatica . Nitrification-denitrification accounted for 86.35% of TN loss in A. calamus . These findings helped to insight into N removal mechanisms in different plants.